2015
DOI: 10.1016/j.jpsychires.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in depressed postpartum women: Associations with childhood trauma, sleep disturbance and anxiety

Abstract: Background Suicide is one of the leading causes of death in postpartum women. Identifying modifiable factors related to suicide risk in mothers after delivery is a public health priority. Our study aim was to examine associations between suicidal ideation (SI) and plausible risk factors (experience of abuse in childhood or as an adult, sleep disturbance, and anxiety symptoms) in depressed postpartum women. Methods This secondary analysis included 628 depressed mothers at 4–6 weeks postpartum. Diagnosis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 103 publications
(132 reference statements)
5
67
0
1
Order By: Relevance
“…This is concerning, given our study is not limited to mothers experiencing postpartum depression or other psychiatric morbidities. Our study supports the findings of Sit et al (2015) that postpartum endorsement of SI is amplified in the context of CM history and extends this research to include longitudinal observation, and validated assessments of trauma history. Additionally, the high rates of SI throughout later postpartum (i.e., 12-, 15-, and 18-months postpartum), suggest that parenting a toddler may confer continued stressors for mothers beyond the early infancy period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is concerning, given our study is not limited to mothers experiencing postpartum depression or other psychiatric morbidities. Our study supports the findings of Sit et al (2015) that postpartum endorsement of SI is amplified in the context of CM history and extends this research to include longitudinal observation, and validated assessments of trauma history. Additionally, the high rates of SI throughout later postpartum (i.e., 12-, 15-, and 18-months postpartum), suggest that parenting a toddler may confer continued stressors for mothers beyond the early infancy period.…”
Section: Discussionsupporting
confidence: 86%
“…It may also be that particular types of CM confer particular longitudinal risk. For example, Sit et al, (2015) observed that childhood physical abuse but not childhood sexual abuse was associated with SI at 6-weeks postpartum. Future research needs to examine if different types of maltreatment are associated with SI among postpartum women with maltreatment histories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported that childhood physical and emotional abuse and childhood neglect are directly related to suicidal ideation, whereas some studies have reported that childhood physical and emotional abuse are associated with anxiety 474849. Recently it was reported that among women with postpartum depression, having frequent thoughts about self-harm was associated with childhood physical abuse and anxiety symptom 50. In light of these findings our results suggest that anxiety plays an important role as a mediator of the relationship between childhood maltreatment and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…The postpartum period is characterized by multiple concerns involving self‐confidence, mother–infant interaction, body image experiences, adjustment to maternal roles, and attitudes . These concerns—which are not only dependent on the presence or diagnosis of morbidity, but also on the inadequate assessment of such issues or even their misinterpretation—may contribute to the deterioration of maternal and newborn health …”
Section: Introductionmentioning
confidence: 99%